2011
DOI: 10.1262/jrd.10-186k
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Trophoblast-Specific Factors by GATA2 and GATA3 in Bovine Trophoblast CT-1 Cells

Abstract: Abstract. Numerous transcription factors that regulate trophoblast developmental processes have been identified; however, the regulation of trophoblast-specific gene expression has not been definitively characterized. While a new role of Gata3 in trophoblast development was being demonstrated in mice, we examined effects of GATA transcription factors on conceptus interferon tau (IFNT), a major trophectoderm factor in ruminants. In this study, expression patterns of trophoblast ASCL2, CDX2, CSH1, ELF5, HAND1, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Recently, we found that GATA2 and GATA3 could also increase IFNT transcription in our transient transfection system [15,16]. During the peri-attachment period, changes in IFNT, GATA2, and GATA3 expression are similar, and the expression of these proteins declines following conceptus attachment to the uterine epithelium [15,16]. In our experiment, GATA6 expression increased after conceptus attachment to the uterine epithelium (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Recently, we found that GATA2 and GATA3 could also increase IFNT transcription in our transient transfection system [15,16]. During the peri-attachment period, changes in IFNT, GATA2, and GATA3 expression are similar, and the expression of these proteins declines following conceptus attachment to the uterine epithelium [15,16]. In our experiment, GATA6 expression increased after conceptus attachment to the uterine epithelium (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…The numerous transcription factors found thus far as regulators of IFNT genes include ETS2 [30,31], activating protein 1 (AP-1; official symbol JUN) [32], CDX2 [24,27], homeobox protein distal-less 3 (DLX3) [33], and co-activators cAMP-response element binding protein (CREB)-binding protein (CREBBP) [34] and p300 [35]. Recently, we found that GATA2 and GATA3 could also increase IFNT transcription in our transient transfection system [15,16]. During the peri-attachment period, changes in IFNT, GATA2, and GATA3 expression are similar, and the expression of these proteins declines following conceptus attachment to the uterine epithelium [15,16].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Some elements, AP2, GATAs, PURA, and SPs, have been reported as activation factors for this gene, and CSH1 expression was closely related to the implantation process spatiotemporally (Limesand et al 2004, Jeckel et al 2009). GATA may play a regulatory role of CSH1 expression and differentiation of BNCs (Bai et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The genes in the “Trophoblast Core” included many that have been reported in elongating trophoblasts (D12-D18: AKR1B1 , GATA2 , GATA3 , PAG2 , PCSK3 , TKDP [28]), trophoblast cell lines (bovine CT1, D10-11: GATA2 , GATA3 , PAG [29]), early trophectoderm (bovine D7 blastocysts: FABP5 , GATA2 , SLC15A1 [30]), or chorionic trophoblast stem cells ( PEG3 [31]). Most genes, however (41 out of 56), were new in the bovine trophoblast, including some involved in cell adhesion regulation and epithelial sheet morphogenesis.…”
Section: Resultsmentioning
confidence: 99%